Intervensi Digital Terapi SEFT Terhadap Gangguan Kecemasan pada Remaja Pasca Bencana Banjir Rob di Pinggiran Sungai Kapuas Wilayah Kerja Puskesmas Tambelan Sampit - Nurul Hidayah; Florensa; Nisma; Nurul Jamil (MES Bogor, 2024)
The Kapuas Riverbanks area is highly prone to tidal flooding (rob floods) due to tidal influences and rising river water levels. Recurring tidal floods not only cause physical damage but also impact the psychological well-being of the affected communities, particularly adolescents. Adolescents, as a vulnerable group, face emotional and social challenges, making them more susceptible to anxiety disorders triggered by the uncertainty and stress caused by such disasters, such as the threat of losing their homes, disruptions to daily activities, and concerns about their future.This study aims to analyze the effectiveness of digital SEFT (Spiritual Emotional Freedom Technique) therapy in alleviating anxiety disorders among adolescents affected by tidal flooding in the operational area of Tambelan Sampit Community Health Center. The study employs a Quasi-Experimental design with a pre-test and post-test approach. Anxiety levels were measured using the HARS (Hamilton Anxiety Rating Scale), which has been digitally integrated into an Android-based application to facilitate accessibility and improve data collection accuracy. The results indicate that digital SEFT therapy significantly reduces anxiety scores in adolescents affected by tidal flooding. This demonstrates that a digital-based approach offers a practical and effective solution for supporting adolescent mental health in disaster-prone areas. The study recommends incorporating digital SEFT therapy into psychological disaster response programs, especially for addressing the psychological impacts of tidal flooding, to efficiently reach broader populations.